Hearts unbroken ebook - Smith, Cynthia Leitich (2018)
New York Times best-selling author Cynthia Leitich Smith turns to realistic fiction with the thoughtful story of a Native teen navigating the complicated, confusing waters of high school — and first love. When Louise Wolfe's first real boyfriend mocks and disrespects Native people in front of her, she breaks things off and dumps him over e-mail. It's her senior year, anyway, and she'd rather spend her time with her family and friends and working on the school newspaper. The editors pair her up with Joey Kairouz, the ambitious new photojournalist, and in no time the paper's staff find themselves with a major story to cover: the school musical director's inclusive approach to casting The Wizard of Oz has been provoking backlash in their mostly white, middle-class Kansas town. From the newly formed Parents Against Revisionist Theater to anonymous threats, long-held prejudices are being laid bare and hostilities are spreading against teachers, parents, and students — especially the cast members at the center of the controversy, including Lou's little brother, who's playing the Tin Man. As tensions mount at school, so does a romance between Lou and Joey — but as she's learned, "dating while Native" can be difficult. In trying to protect her own heart, will Lou break Joey's?